The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fcimb.2023.1242681
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the gut microbiome and its metabolites are associated with the immune response to mucosal immunization with Lactiplantibacillus plantarum-displaying recombinant SARS-CoV-2 spike epitopes in mice

In-Chan Hwang,
Robie Vasquez,
Ji Hoon Song
et al.

Abstract: Lactic acid bacteria (LAB) expressing foreign antigens have great potential as mucosal vaccines. Our previous study reported that recombinant Lactiplantibacillus plantarum SK156 displaying SARS-CoV-2 spike S1 epitopes elicited humoral and cell-mediated immune responses in mice. Here, we further examined the effect of the LAB-based mucosal vaccine on gut microbiome composition and function, and gut microbiota-derived metabolites. Forty-nine (49) female BALB/c mice were orally administered L. plantarum SK156-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Limosilactobacillu and Lactobacillus are a group of Gram-positive bacteria under the family Lactobacillaceae of the thick-walled phylum. Their ability to enhance the physical barrier of the mucus layer to improve immunity, their ability to produce lactic acid to maintain a weakly acidic environment as a major metabolic end product of carbohydrate fermentation ( Petrova et al., 2015 ; Li C. et al., 2023 ), and modulation of Muribaculaceae abundance may ameliorate metabolic disorders by altering metabolism and butyrate production, and modulation of antibody and anti-inflammatory cytokine production to ameliorate inflammation ( Hwang et al., 2023 ). In the present study, we found that the intestinal microbiota of Muribaculaceae , Limosilactobacillus and Lactobacillus were reduced in the CP group of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Limosilactobacillu and Lactobacillus are a group of Gram-positive bacteria under the family Lactobacillaceae of the thick-walled phylum. Their ability to enhance the physical barrier of the mucus layer to improve immunity, their ability to produce lactic acid to maintain a weakly acidic environment as a major metabolic end product of carbohydrate fermentation ( Petrova et al., 2015 ; Li C. et al., 2023 ), and modulation of Muribaculaceae abundance may ameliorate metabolic disorders by altering metabolism and butyrate production, and modulation of antibody and anti-inflammatory cytokine production to ameliorate inflammation ( Hwang et al., 2023 ). In the present study, we found that the intestinal microbiota of Muribaculaceae , Limosilactobacillus and Lactobacillus were reduced in the CP group of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites produced by some bacteria can target the S protein of coronaviruses, thereby improving dysbiosis. 110 , 111 The reduced diversity of intestinal flora in patients with COVID can be accompanied by changes in circulating and intestinal SCFAs and an imbalance in circulating immune cell subsets. The proportions of CD19 + B, CD4 + T, CD8 + T, and NK cells of patients with COVID‐19 were significantly decreased, and the IL‐6 and IL‐10 levels were significantly increased, all of which were more prominent in critically ill patients.…”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%
“…In turn, the gut microbiome and its metabolites may influence the immunogenicity of SARS‐CoV‐2 vaccines. 111 , 136 Although the mechanism of this vaccine‐induced change in the microbiota and the bidirectional regulation of metabolites and inflammatory immune response caused by the changes in the microbiota has not been elucidated, exploring the relevant mechanisms provides new ideas for the optimization of vaccines and the selection of adjuvants. Vaccine‐associated microbiota changes and the potential bidirectional regulation are shown in Figure 5 .…”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%